Favoritism by the governing elite - Zareh Asatryan; Thushyanthan Baskaran; Carlo Birkholz; Patrick Hufschmidt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
In this paper, we study the extent to which ministers engage in regional favoritism. We are the first to provide a comprehensive analysis of a larger set of the governing elite, not just focusing on the primary leader. We hand-collect birthplaces of this governing elite globally. Combining this information with extended night-time luminosity and novel population data over the period from 1992 to 2016, we utilize a staggered difference-in-differences estimator and find that birthplaces of ministers globally emit on average roughly 7% more nightlight. We do not find evidence that this is driven by, or induces migration to their home regions. The size of our data set lets us investigate heterogeneities along a number of dimensions: political power, ministerial portfolio, and the institutional setting.
Keywords: D72; H72; H77; R11; 330; Favoritism; elite capture; spatiality; luminosity; population; democracy